2012
DOI: 10.1007/s00259-012-2145-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery injection of 131I-labelled metuximab combined with chemoembolization for intermediate hepatocellular carcinoma: a prospective nonrandomized study

Abstract: The combination of (131)I-metuximab and chemoembolization extended survival in patients with intermediate HCC compared with TACE only, and was well tolerated by patients with Child-Pugh class A or B disease. This combination seems to be a promising treatment modality for patients with intermediate HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Metuzumab, as an anti-CD147 mAb, may induce adverse side effects in liver and blood compartments; however, toxicity study results showed that it was well tolerated in rat and monkey models. Some clinical trials also suggested that anti-CD147 therapy appears to be a safe and effective treatment of cancer (23,24,(43)(44)(45). Overall, careful attention should be focused on monitoring blood, liver, and muscle function impairments in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Metuzumab, as an anti-CD147 mAb, may induce adverse side effects in liver and blood compartments; however, toxicity study results showed that it was well tolerated in rat and monkey models. Some clinical trials also suggested that anti-CD147 therapy appears to be a safe and effective treatment of cancer (23,24,(43)(44)(45). Overall, careful attention should be focused on monitoring blood, liver, and muscle function impairments in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The full-texts were carefully evaluated. They were published from 2007 to 2015, and all had investigated TACE plus 131 I-metuximab therapy (1112131920212223). Totally 1121 patients were included in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among those, 546 patients underwent TACE plus 131 I-metuximab therapy, as compared with 575 patients who received TACE alone. There were: 3 RCTs (112223), and 5 non-RCTs (1213192021) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…156 In another Hepatocellular treatment trial, this combination had acceptable outcomes for intermediate stage HCC and it was suggested as a therapeutic option for this stage. 157 In another study efficacy of the combination of TACE and brachytherapy was compared to TACE alone. The study group had combination of loboplatin-TACE and 125 I seeds as radiotherapy.…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 99%